Traktor Modern Berbasis pH dan NPK Sensors Guna Meningkatkan Produktivitas dan Kualitas Tanaman di Desa Madiredo Kabupaten Malang - Agung Witjoro; Mohammad Rodhi Faiz; Budi Wibowotomo; Sujito; Revanza Akiella Jihan Putra; Abdullah Iskandar Syah (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Agriculture is a crucial sector in supporting food security and the national economy. However, the limited use of modern technology remains a barrier to increasing farmer productivity. The partner for this community service activity is the HARAPAN Farmers Group in Sobo Hamlet, Madiredo Village, Pujon District, Malang Regency, which manages approximately 0.5 hectares of land with an average yield of 30 tons of vegetables per harvest. The partner's main problems include the use of time-consuming conventional tools, suboptimal soil quality, and harvests that do not meet market standards. The solution offered is the implementation of a modern tractor based on pH and NPK sensors integrated with the NANDUR application. This application functions to monitor soil conditions, provide suggestions for suitable plant types, and display information related to cultivation. The implementation of this technology has been proven to increase work efficiency by speeding up the land processing process from 10 hours to 5 hours and helping farmers understand land conditions for appropriate decision-making. This activity is expected to increase productivity, the quality of agricultural products, and the welfare of farmers in a sustainable manner.